Russia`s regional disharmonies in team sport development process: pareto diagram data analysis - Petrov, A. I.; Petrova, D. A. (Theory and Practice of Physical Culture, 2019)
Objective of the study was to analyze regional irregularities in the team sport progress using Pareto Diagram to quantify and profile the regional contributions to the national competitive successes. The study was designed to rate and compare the regional contributions to the national total; plus analyze the competitive progress on a year-to-year basis (2015 to 2014, and 2018 to 2017, as of January 1). The Pareto Diagram was formed in a few stages: regional team sports progress in points was rated at stage 1; and the regional contributions to the national total competitive success were weighted at stage 2. Having the team sport progress scores for every Russian region, we could compute the elementary regional sport clubs` contributions to the national total. These data were analyzed to produce the summarized curve to visualize and quantify the regional disharmonies/ irregularities in the team sports progress domain.